Boletim da Previdência Social - Ministério do Trabalho e Previdência Social (M.T.P.S.)
Existências: A. 1 , nº 2 (Jan.-Mar. 1917) - Nº 15 (Jan.- Dez. 1924) Nº 19 (Jan.- Jul. 1928) Nº 15 (Jan.- Dez. 1924)